Evaluasi Keberhasilan Sistem Informasi Universitas - Agus Prasetyo Utomo; Novita Mariana; Saefurrohman Saefurrohman (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Information system success evaluation research is not a new research topic. However, studying the factors that influence the success of information systems in universities is one that is quite interesting for some researchers. This study aims to examine how the influence of information quality, system quality, and service quality on satisfaction and the effect on net benefits perceived by users of university information systems. As many as 180 undergraduate and graduate students from 6 faculties at Stikubank University taken part in this study. The partial least squares-structural equation modeling (PLS-SEM) approach is used to validate the research model. Empirical results show that information quality, system quality and service quality have a significant positive relationship with user satisfaction for using university information systems, while user satisfaction also shows a significant negative relationship with system user perceived net benefits. The results obtained from this study provide reinforcement of the findings from previous studies related to the evaluation of information system success models. Keywords:.